Strangers and Friends at the Welcome Table : Contemporary Christianities in the American South - Hudnut-Beumler, James David (Book collections on Project MUSE., 2018)
"In this fresh and fascinating chronicle of Christianity in the contemporary South, historian and minister James Hudnut-Beumler draws on extensive interviews and his own personal journeys throughout the region over the past decade to present a comprehensive portrait of the South's long-dominant religion. Hudnut-Beumler traveled to both rural and urban communities, listening to the faithful talk about their lives and beliefs. What he heard pushes hard against prevailing notions of southern Christianity as an evangelical Protestant monolith so predominant as to be unremarkable"--